2020
DOI: 10.3389/fcimb.2020.581888
|View full text |Cite
|
Sign up to set email alerts
|

Shifts in the Bacterial Community of Supragingival Plaque Associated With Metabolic-Associated Fatty Liver Disease

Abstract: Metabolic-associated fatty liver disease (MAFLD), also known as the hepatic manifestation of metabolic disorders, has become one of the most common chronic liver diseases worldwide. The associations between some oral resident microbes and MAFLD have been described. However, changes to the oral microbial community in patients with MAFLD remain unknown. In this study, variations to the supragingival microbiota of MAFLD patients were identified. The microbial genetic profile of supragingival plaque samples from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 61 publications
4
12
0
Order By: Relevance
“…(Liu et al, 2015) are generally Gram-negative microorganisms comprising mainly non-pathogenic species in the oral cavity. Previously, we also demonstrated a higher abundance of Neisseria in the supragingival plaque among healthy individuals compared to those with MAFLD (Zhao et al, 2020). Capnocytophaga is a genus of Gram-negative anaerobic bacteria reportedly linked with improved oral health and reduced caries experience (Schoilew et al, 2019).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…(Liu et al, 2015) are generally Gram-negative microorganisms comprising mainly non-pathogenic species in the oral cavity. Previously, we also demonstrated a higher abundance of Neisseria in the supragingival plaque among healthy individuals compared to those with MAFLD (Zhao et al, 2020). Capnocytophaga is a genus of Gram-negative anaerobic bacteria reportedly linked with improved oral health and reduced caries experience (Schoilew et al, 2019).…”
Section: Discussionmentioning
confidence: 75%
“…shtml ). The specific criteria are consistent with the previous study (Zhao et al, 2020). UPARSE (version 7.1, http://drive5.com/uparse/) was used to cluster the sequences into operational taxonomic units (OTUs) with a threshold of 97% similarity.…”
Section: Data Processing and Bioinformatics Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous observational and interventional studies have linked IR to PDD ( 49 ). IR was positively correlated with the abundances of Granulicatella , Veillonella , Streptococcus , and Scardovia in supragingival plaque by 16s rDNA sequencing in patients with metabolism-associated fatty liver disease ( 50 ). A previous study has demonstrated that IR was associated with the abundance of 22 individual taxa in human subgingival plaque ( 51 ).…”
Section: Potential Mechanisms By Which Pcos Might Increase the Risk O...mentioning
confidence: 99%